Da’wah in community development: Analysis of community development methods in the Al-Qur’an - Achmad Ghozali; Yulia Annisa; Muhlasin Muhlasin (Jurnal Ilmu Dakwah, 2022)
Objective - The objective of this study focuses on analyzing the Qur'anic concept of empowerment methods to anticipate the negative impacts of modernization by grounding Islamic teachings through community empowerment with the concept of development that must be comprehensive, touching, and penetrating human identity.Method - The study method is carried out through a literature study, with content analysis techniques.Result - The results of this study analyzed 3 methods, they are 1) the al-Hikmah method a) through comparative (comparison), b) through proverbs (examples), c) through history (stories). 2) Method of Da'wah al-Mau'izhah al hasanah; a) Education and teaching, b) Guidance and counseling. c) uswahwa al-tathbiq (good example). 3) Da'wah al-Mujlah hiya ahsan method a) Deliberation of FGD (Focus Group Discussion), b) Muzakarah (Participatory Learning and Action), or Participatory Learning and Practice Processes). c) Mubahalah (Farmers Field School) or Field School.Implication – This method suggests enriching insight and a comparison with empowerment theories discussed from the current concepts and improving the performance of Islamic community empowerment skills.Originality - The focus of this research produces an empowerment method that is not only limited to the aspect of material welfare but can build a whole person, from all material and spiritual aspects simultaneously.  ***Tujuan - Tujuan penelitian ini adalah untuk menganalisis konsep Al-Qur'an metode pemberdayaan untuk mengantisipasi dampak negatif modernisasi dengan membumikan ajaran Islam melalui pemberdayaan masyarakat dengan konsep pembangunan yang harus komprehensif, menyentuh, dan menembus identitas manusia.Metode – Metode penelitian dilakukan melalui studi pustaka, dengan teknik analisis isi.Hasil - Hasil penelitian ini menganalisis 3 metode yaitu 1) metode al-Hikmah a) melalui komparatif (perbandingan), b) melalui peribahasa (contoh), c) melalui sejarah (cerita). 2) Metode Dakwah al-Mau'izhah al hasanah; a) Pendidikan dan pengajaran, b) Bimbingan dan konseling. c) uswahwa al-tathbiq (teladan yang baik). 3) Metode Dakwah al-Mujlah hiya ahsan a) Musyawarah FGD (Focus Group Discussion), b) Muzakarah (Pembelajaran dan Tindakan Partisipatif), atau Proses Pembelajaran dan Praktek Partisipatif). c) Mubahalah (Sekolah Lapangan Petani) atau Sekolah Lapang.Implikasi – Metode ini menyarankan pengayaan wawasan dan pembandingan dengan teori-teori pemberdayaan yang dibahas dari konsep-konsep yang ada dan peningkatan kinerja keterampilan pemberdayaan masyarakat Islam.Orisinalitas - Fokus penelitian ini menghasilkan suatu metode pemberdayaan yang tidak hanya terbatas pada aspek kesejahteraan material tetapi dapat membangun manusia seutuhnya, dari seluruh aspek material dan spiritual secara bersamaan.